UPACARA ADAT SEREN TAUN UPAYA MEMPERTAHANKAN NILAI KEARIFAN LOKAL MASYARAKAT KAMPUNG SODONG KECAMATAN TAMBAKSARI KABUPATEN CIAMIS TAHUN 2003-2011 - Widiati Isana (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2017)
Seren Taun traditional ceremony is very interesting to study and explore further, considering that traditional culture is a heritage that today is increasingly sidelined and forgotten. Though it contains the values of local wisdom that is able to develope togetherness and  envolve character of the dignity of Indonesian people. The purpose of this study is to determine the profile of Kampung Sodong Tambaksari Ciamis, implementation of traditional ceremony Seren Taun and maintaining the local wisdom values of Kampung Sodong Tambaksari Ciamis particularly in 2003 -2011. This research starting point from the conceptual framework that changes can occur because of the emergence of response to social phenomena around the people.Seren Taun traditional ceremony is a generated process of challenge and local wisdom value is  response that interacts showing certain patterns in its development. This study uses historical method .Type of data is qualitative, data collection techniques through interviews , documents , and literature study. The results shows that the profile of Kampung Sodong Tambaksari Ciamis in 2003 showed the big potential of village in various fields . Seren Taun traditional ceremony was a handover years ago to the coming year, as the way for celebration thankfulness and hope.This custom event encourages the community to maintain the values of local wisdom that can improve the character of the nation's dignity.